Cell Physiology in Tissue Slices Studying Beta Cells in the Islets of Langerhans : Celična fiziologija v tkivnih rezinah - Preučevanje celic beta v Langerhansovih otočkih - Stožer, Andraž; Dolenšek, Jurij; Skelin Klemen, Maša; Slak Rupnik, Marjan (Acta Medico-Biotechnica, 2021)
Isolated endocrine cells have enabled the development of numerous methods to assess basic cellular architecture and define a significant part of the molecular machinery involved in cellular processes, such as excitability or the exocytotic release of hormones following cytosolic calcium increase. These efforts have generated consensus models explaining the activation or general operation of a particular cell type. The use of fresh tissue slices can go even further and uncover a series of emergent properties never explained orpredicted by consensus models. In this paper, we present a selection of our most important experimental findings in the beta cells of pancreatic tissue slices.